2011
DOI: 10.5301/jva.2011.6390
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Eye to Eye: The Key to Reducing Catheter Use

Abstract: The primary reasons patients use CVCs are "non-medical" followed by concerns with the complications and esthetic appearance associated with fistulas/grafts. The significant discordance between the reasons the patients give and the VAC's view of patient reasons for CVC use suggests a gap in knowledge, understanding, or communication between patients and their VACs. Timely predialysis education to address this gap and realistic targets are necessary to reduce CVC prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
1
37
0
2
Order By: Relevance
“…Further, these failures may lead patients to doubt the overall benefit of fistulas. Patient refusal is a significant barrier to fistula creation: Currently, up to 30% of eligible patients decline fistula creation (24,(45)(46)(47). In a novel qualitative study conducted by Xi et al, negative personal or vicarious experience with a fistula emerged as a major reason for patient refusal of a fistula (45).…”
Section: Discussionmentioning
confidence: 99%
“…Further, these failures may lead patients to doubt the overall benefit of fistulas. Patient refusal is a significant barrier to fistula creation: Currently, up to 30% of eligible patients decline fistula creation (24,(45)(46)(47). In a novel qualitative study conducted by Xi et al, negative personal or vicarious experience with a fistula emerged as a major reason for patient refusal of a fistula (45).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, only 24% of patients had no preference; 12% preferred a CVC (nonblack women had the highest CVC preference at 17%). The most common reasons for preferring a CVC were no puncture and no bleeding, avoidance of disfigurement, and better cosmesis (51,54). The DOPPS survey revealed that up to 20% of patients received little or no vascular accessrelated education, suggesting that they did not fully understand the risks and benefits of various vascular access types.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Depending on whether the patients are predialysis or on dialysis, they would have had differing exposures and experiences with AV accesseither their own or shared by other patients in waiting rooms or on dialysis. As clinicians, we are concerned about the AV access type and their associated complications; however, patients may have far differing concerns (50,51). Patients are much more worried about daily quality of life issues with their vascular access, such as pain with cannulation, and influenced by their prior experiences with a failed AV access that required painful interventions.…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that our entire cohort was relatively young and that acute kidney injury in the kidney transplant setting is more frequent in younger individuals [31] could possibly explain these findings. Equally important, esthetic concerns related to permanent dialysis access [32] and an unwillingness to commit to a dialysis modality during the predialysis period may be more frequent in the younger age group.…”
Section: Discussionmentioning
confidence: 99%